FDOPA PET-CT of Nonenhancing Brain Tumors. (April 2017) - Bund, Caroline; Heimburger, Céline; Imperiale, Alessio; Lhermitte, Benoît; Chenard, Marie-Pierre; Lefebvre, François; Kremer, Stéphane; Proust, François; Namer, Izzie-Jacques
Abstract : Background: Primary brain tumor grading is crucial to rapidly determine the therapeutic impact and prognosis of a brain tumor as well as the tumors' aggressiveness profile. On magnetic resonance imaging, high-grade tumors are usually responsible for blood -brain barrier breakdowns, which result in tumor enhancement. However, this is not always the case. The main objective of this study was to evaluate the diagnostic value of FDOPA PET in the assessment of primary brain tumor aggressiveness with no contrast enhancement on MRI. Methods: Fifty-three patients were prospectively included: 35 low-grade and 18 high-grade histologically proven gliomas, with no contrast enhancement. Each patient underwent static PET acquisitions at 30 minutes. All patients had MRSI with measurements of different metabolites ratio. Results: FDOPA was useful in the subgroup of low-grade gliomas, discriminating between dysembryoplastic neuroepithelial tumor and grade II oligodendroglioma ( P < 0.01). An optimal threshold of the maximum standardized uptake value at 30 minutes (SUVmax (T/N)30 ) = 2.16 to discriminated low- from high-grade gliomas with a sensitivity of 60%, specificity of 100%, PPV of 100%, and NPV of 83.33% ( P < 0.01). The nCho/Cr and nCho/NAA ratios were significantly higher in high- than in low-grade gliomas ( P < 0.03 and P < 0.04, respectively). A significant positive correlation between MRSI ratios and SUVmax was found. Conclusion: Including data from amino acid metabolism used alone or in association with MRSI allows us to discriminate between dysembryoplastic neuroepithelial tumor and grade II oligodendroglioma and between low- and high-grade gliomas with no contrast enhancement on MRI.